Productivity improvement through line balancing - Hazmil, Hapaz (2008)
Poor layout design is determine as a major problem contribution in small and medium industry. These particular problems thus affect the productivity and the line efficiency as well. Throughout the study, the aim is to proposed new layout to the related company to increase their productivity. The major step is to identify a bottleneck workstation in current layout. After identify related problems, the current layout is redesign by computing the standard time and processing time in each workstations. In each workstation the processing time is different and the longest time consumption is workstation will be identified as a bottleneck workstation. This related line is studied by time study techniques. The time is taken by stopwatch. In this study, application of Computer Aided tools is introduced which in this study is WITNESS SOFTWARE. The related inputs are going to be simulated with this software. The manual calculation also included especially in line balancing algorithm. The goal of the thesis is to seek the best layout in terms of line efficiency and productivity rate hence proposed to the company. Through out the study, 3 layouts have been achieved. Among 3 layouts only one will be propose to the company. This layout has better line efficiency and rate of productivity.